2010
DOI: 10.1042/bj20091302
|View full text |Cite
|
Sign up to set email alerts
|

The substrates and binding partners of protein kinase Cε

Abstract: The epsilon isoform of protein kinase C (PKCε) has important roles in the function of the cardiac, immune and nervous systems. As a result of its diverse actions, PKCε is the target of active drug discovery programs. A major research focus is to identify signaling cascades that include PKCε and the substrates that PKCε regulates. In this review we will identify and discuss those proteins that have been conclusively shown to be direct substrates of PKCε by the best currently available means. We will also descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 109 publications
(135 reference statements)
2
58
0
Order By: Relevance
“…Consistently, the down-regulation of PKC-ε also attenuated breast cancer growth in vivo. These results agree with those by Newton and Messing showing that uncontrolled PKCɛ activation is associated with cancer development [37]. Given that different PKC isoforms may display a distinct functional role in the control of normal and cancer cell fates [6][7][8][38][39][40], the inhibition of PKC-ε may be an attractive therapeutic strategy not only for treating proliferative VSMC-related diseases, such as atherosclerosis and restenosis, but also for targeting certain types of cancer like breast cancer.…”
Section: Discussionsupporting
confidence: 81%
“…Consistently, the down-regulation of PKC-ε also attenuated breast cancer growth in vivo. These results agree with those by Newton and Messing showing that uncontrolled PKCɛ activation is associated with cancer development [37]. Given that different PKC isoforms may display a distinct functional role in the control of normal and cancer cell fates [6][7][8][38][39][40], the inhibition of PKC-ε may be an attractive therapeutic strategy not only for treating proliferative VSMC-related diseases, such as atherosclerosis and restenosis, but also for targeting certain types of cancer like breast cancer.…”
Section: Discussionsupporting
confidence: 81%
“…When stimulated by PMA, isoforms of PKC regulate the machinery that controls the intracellular trafficking and transport of proteins; for example, PKC⑀ stimulates membrane trafficking through binding of ␤'COP, a coatomer protein, and regulates the function of cytoskeletal components (25). We and others have shown that PMA stimulates the trafficking of MT1-MMP to the plasma membrane (17,26).…”
Section: Pma Stimulates Mt1-mmp Phosphorylation-phorbolmentioning
confidence: 99%
“…20 Specifically, PKCe, unlike other PKC family members, contains an F-actinbinding region that promotes the formation of F-actin filaments by preventing depolymerization and increasing the rate of actin filament elongation. 21 During mitotic cytokinesis of several cell types (ie, COS-7, HeLa, MEF, HEK 293), PKCe assembles with 14-3-3zeta, and together they transiently accumulate at the actomyosin ring with RhoA and is required to dissociate both itself and RhoA from the midbody. 22 In neurons, PKCe promotes neurite outgrowth, which can be blocked by forced activation of the ROCK/RhoA pathway, indicating that PKCepilson may attenuate RhoA/ROCK pathway activity in the process.…”
Section: Introductionmentioning
confidence: 99%